Soil Carbon in The Bone Bay Mangrove Ecosystem, Palopo City - Srida Mitra Ayu; Nardy Noerman Najib; Witno Witno; Angger Angger (Jurnal Biodjati, 2022)
The mangrove ecosystem is one of the many ecosystems found along tropical beaches that have a function as a buffer area between land and sea and produce organic matter. There are several factors that influence the spread of mangrove plants, namely the physical factor of the soil. This study aimed to determine the soil carbon content in the mangrove ecosystem in the village of Temmalebba, South Sulawesi. The data collected in the form of bulk density (BD), organic matter (BO) and percent C for analysis of carbon content was obtained from the analysis of soil samples taken from 10 points with 3 replications for composite samples. The sampling point was determined based on the growth and density of mangroves. Furthermore, the data was analyzed using the organic C equation and carbon content. The results showed that the highest bulk density was found at a depth of 60–100 cm with a value of 1.28 g/cm3. The highest percent of organic matter content found at a depth of 0-30 cm with a value of 9.18%. The highest soil carbon content found at a depth of 60–100 cm with a value of 225.38 (MgC ha-1). Soil carbon content in the mangrove ecosystem of Bone Bay, Temmalebba village is strongly influenced by several factors, including soil depth, bulk density, organic matter, and soil texture.